Dictionary Usage In English Language Learning - Rohmatillah, Rohmatillah (English Education: Jurnal Tadris Bahasa Inggris, 2016)
This article examined about the important of using dictionary in English language learning. We cannot deny in learning a foreign language, we need to consult a dictionary. It is supported by Laufer in Koca believes that when word looks familiar but the sentence in which it is found or its wider context makes no sense at all, the learner should be encouraged to consult a dictionary. Sometimes the learners are reluctant to find out the other meaning of word  from dictionary, as a result the meaning of that word is not based on the context of the sentence. This article also discussed about types and purpose of using dictionary, criteria of good dictionary, monolingual and bilingual dictionary use and skills in using dictionary.